Betatrophin association with serum triglyceride levels in obstructive sleep apnea patients - Bunyamin Sertogullarindan (Annals of Thoracic Medicine, 2019)
BACKGROUND: Obstructive sleep apnea (OSA) is a common sleep problem, in which patients are at increased risk for metabolic and cardiovascular problems, including metabolic syndrome, diabetes mellitus (DM), and dyslipidemia. Betatrophin is a novel protein that regulates fatty acid and triglyceride (TG) metabolism and is related to obesity and metabolic abnormalities, including metabolic syndrome, DM, and dyslipidemia. Although OSA and betatrophin share common abnormalities, their relationship has not been investigated. AIM: The aim of this study is to investigate the relationships among betatrophin, OSA, and the serum lipid profile. METHODS: Ninety consecutive patients with suspected OSA underwent polysomnography (PSG) to confirm OSA. Plasma betatrophin, leptin, adiponectin, and the full lipid profile were analyzed. The patients were categorized as OSA or control based on the apnea-hypopnea index (AHI). RESULTS: About 61% of patients had OSA, and 39% had normal PSG. The levels of betatrophin, leptin, and adiponectin were higher in patients with OSA (256.59 ± 29.35, 374.20 ± 37.93, and 17.86 ± 2.63 μg/mL, respectively) compared to the controls (141.86 ± 26.20, 205.53 ± 14.75, and 7.52 ± 1.02 μg/mL, respectively). Betatrophin levels were correlated with the AHI, leptin (r = 0.413, P = 0.002, r = 0.782, P = 0.000). TG levels were significantly higher, and high-density lipoprotein cholesterol (HDL-C) levels were lower, in OSA patients compared to controls (244 ± 20.33 vs. 138 ± 14.89, and 37.21 ± 1.26 vs. 43.78 ± 1.62, respectively). The TG level was correlated with betatrophin (r = 0.353, P = 0.013). Multiple regression analysis showed that the AHI, leptin, and arousals were independent predictors of betatrophin level (B = 1.70 P = 0.046 95%, B = 0.56 P < 0.005, and B = 1, 2, P = 0.003, respectively). CONCLUSIONS: Our results suggest a complex relationship between OSA, betatrophin, TG, and HDL, as well as other adipokines. Our results require further investigation to assess this complex association and re-evaluate previous related studies.